(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides an in-depth exploration of adverbs, focusing on their grammatical categories and syntactic functions. It begins by defining adverbs as words that modify verbs, adjectives, other adverbs, and entire clauses, outlining their role in conveying nuances of time, manner, frequency, degree, and certainty. The article then categorizes adverbs semantically (based on meaning), morphologically (based on formation), and syntactically (based on sentence position), illustrating their versatility in